APLIKASI DOA-DOA YAJNA HINDU BERBASIS ANDROID (STUDI KASUS PADA PEMUDA DAN PEMUDI HINDU DESA JEMBRANA, KEC. WAWAY KARYA, KAB. LAMPUNG TIMUR) - Ni Komang Suci; Machudor Yusman; Irwan Adi Pribadi; Made Widhiyana (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Information and communication technology advencements can help humans in obtaining information on various aspects of renewal, one of which is the science of religion. In the teachings of Hinduism, Yajña is a sacred sacrifice committed sincerely. The Sacrifice referred to is an offering made sincerely to Hyang Widhi or God Almighty. The development of technology is very rapid but the lack of media learning Hindu Yajña prayers in digital form so it is very necessary to develop media learning Hindu Yajña prayers in digital form. By utilizing technological developments, it is hoped that memorizing Yajña prayers will be easier and more practical, without having to use books. This research has succeeded in developing an Android-based Hindu Yajña prayer application consisting of worship prayers and 42 prayers including, 15 (fifteen) Mesaiban prayers, 17 (seventeen) Segehan prayers, and 10 (ten) Canang prayers. This application runs on the Android operating system so that it can be accessed by anyone and at any time on a smartphone or tablet computer that supports the Android operating system. The conclusion of this study is that the Android-Based Hindu Yajña Prayers Application has been successfully built and has been tested to match the expected results.